Teachers’ concerns, perception and acceptance towards tauhidic science education - Mohd Salleh, Khalijah; Badzis, Mastura (Centre for Islamic Area Studies at Kyoto University (KIAS), 2011)
There can never be civilization if, within the society, the masses are not educated and developed. Discussion on tauhidic science can be conceptual and philosophical. However such discussions have to be translated into the behavior of not just the scientist themselves but also the masses as well. This means that the discipline of tauhidic science needs to be taught in schools. Hence tauhidic science education is about the implementation of the teaching and learning of tauhidic science in the classroom. Islamic schools in Malaysia offer a curriculum consisting of religious and regular subjects like language, science, and humanities. Currently science and religion, whether in Islamic schools or regular schools, have been taught separately. This is due to the tradition of science that recognize only that which is measureable and repeatable. Knowingly or unknowingly, people just accept that science and religion are separate fields. this is also includes all institution s within the system of education in Malaysia. However, among the Muslim scientist there have already been discussions philosophically and conceptually on Islamic Science (al Farouqi, Syed Naguib, Othman Bakar). In Islam, science and religion are linked in an integrated manner. Such ideas have attracted authorities in some private religious institutions who would like to see that the teaching and learning of science and religion is done in an integrated manner and aligned to the holistic understanding of events, phenomena, and outcome. There are Islamic schools at preschool through secondary levels in Malaysia that have started to offer science lessons. Yayasan Pendidikan Takmir, Kajang, Malaysia is one such example. This school has been one of the pioneer schools interested in integrating science and religion. This is to better position ideas, whether religious or scientific, such that they can help enhance the appreciation of science from the perspective of religion and vice versa. How should this be done? In other words, how can tauhidic science education be implemented in the classroom?